Recognizing and addressing microaggressions in addiction treatment groups: An integrated approach - Steele, Janeé M. (Journal of addictions & offender counseling, 2022)
In this article, the authors draw from multicultural orientation, broaching, and antibias microintervention frameworks to describe an integrated approach to addressing microaggressions during addiction treatment groups. A case study is provided to illustrate the approach and implementation considerations are outlined.